2010
DOI: 10.1007/s12664-010-0034-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of clarithromycin resistance in isolates of Helicobacter pylori from the UAE

Abstract: Clarithromycin resistance was common in this small collection of H. pylori isolates from the UAE. The A2142G and A2143G mutations were associated with clarithromycin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 23 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Subgroup analysis based on PCR methods Several PCR-based methods were applied in these 22 studies. Including FRET-MCA-PCR, 22,25,27,54,[56][57][58] PCR-based sequencing, 52,59,60 TaqMan PCR, 61-64 FISH, 32,33,52,59 allele-specific-PCR, 20,47,65 and dual priming oligonucleotide-PCR, 58 GenoType HelicoDR, 51 PCR-DHPLC, 23 and RFLP-PCR. 31 The results showed that the sensitivity and specificity…”
Section: Performance Of Genotypic Methods In Gastric Biopsy Samplesmentioning
confidence: 99%
“…Subgroup analysis based on PCR methods Several PCR-based methods were applied in these 22 studies. Including FRET-MCA-PCR, 22,25,27,54,[56][57][58] PCR-based sequencing, 52,59,60 TaqMan PCR, 61-64 FISH, 32,33,52,59 allele-specific-PCR, 20,47,65 and dual priming oligonucleotide-PCR, 58 GenoType HelicoDR, 51 PCR-DHPLC, 23 and RFLP-PCR. 31 The results showed that the sensitivity and specificity…”
Section: Performance Of Genotypic Methods In Gastric Biopsy Samplesmentioning
confidence: 99%
“…Unfortunately, resistance to this antibiotic is increasing worldwide and failure treatment is attributed to acquired antibiotic resistance of the organism or lack of compliance with the antibiotic regimen ( 7 ). The prevalence of H. pylori resistance to clarithromycin varies among different countries; 12% in Japan, 1.7% - 23.4% in Europe and 10.6% - 25% in north America ( 5 , 6 , 8 ). Antimicrobial activity of clarithromycin is attributed to inhibition of protein synthesis via attaching to bacterial ribosomal 50S subunit ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance to clarithromycin in H. pylori has been shown to be due to point mutations in the peptidyltransferase region of domain V of the 23S rRNA. The most common mutation is an A-to-G transition at position 2143 (A2143G), but three point mutations -A2142G, A2144G and T2182C -have also been described (Taylor et al, 1997;Alfaresi & Elkoush, 2010). The presence of the A2143G point of mutation has been shown to significantly affect the eradication rate of H. pylori.…”
Section: Introductionmentioning
confidence: 99%